2016
DOI: 10.18632/oncotarget.7005
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497 impairs the growth of chemoresistant neuroblastoma cells by targeting cell cycle, survival and vascular permeability genes

Abstract: Despite multimodal therapies, a high percentage of high-risk neuroblastoma (NB) become refractory to current treatments, most of which interfere with cell cycle and DNA synthesis or function, activating the DNA damage response (DDR). In cancer, this process is frequently altered by deregulated expression or function of several genes which contribute to multidrug resistance (MDR). MicroRNAs are outstanding candidates for therapy since a single microRNA can modulate the expression of multiple genes of the same o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 70 publications
0
23
0
1
Order By: Relevance
“…Proinflammatory cytokines like TNF-α and IL-6 are implicated in inflammation in autoimmune and infectious disease initiation and progression including CIU by activating inflammatory cells and regulating cell differentiation and apoptosis. 43 Another study demonstrated that upregulated miR-21 could decrease vascular permeability in mouse kidneys. 41 TNF-α was upregulated in endothelial and perivascular cells of the upper dermis in CIU inducing neuroendocrine disturbance and susceptibility to CIU, which may be induced by environmental stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines like TNF-α and IL-6 are implicated in inflammation in autoimmune and infectious disease initiation and progression including CIU by activating inflammatory cells and regulating cell differentiation and apoptosis. 43 Another study demonstrated that upregulated miR-21 could decrease vascular permeability in mouse kidneys. 41 TNF-α was upregulated in endothelial and perivascular cells of the upper dermis in CIU inducing neuroendocrine disturbance and susceptibility to CIU, which may be induced by environmental stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that miRNA-34a mimic treatment resulted in a significant decrease in tumor growth, an increase in tumor cell apoptosis and a significant reduction of angiogenesis, suggesting the therapeutic potential of miR-34a mimic in neuroblastoma [77] . A study on the tumor suppressive miR-497 showed that the overexpression of miR-497 reduces tumor growth and inhibits vascular permeabilization in neuroblastoma xenograft model, supporting a potential therapeutic strategy by overexpressing miR-497 [78] .…”
Section: Mirnas In Neuroblastoma Differentiation Therapymentioning
confidence: 96%
“…34 miR-497, proliferasyon, metastaz ve direnç ile ilişkili genleri düzenleyen, hedefe yönelik nöroblastom tedavisi için yeni bir aday molekül-dür. 85 Epigenetik düzenleyici miR-506, TGF-β sinyal yolağında bulunan ROCK1' i inhibe ederek nöroblastom hücrelerinin metastazını baskılamak-tadır. 86 ncRNA 45A'nın upregülasyonu, FE65L1 ve GTSE1 genlerinin ekspresyonunu düzenleyerek tümör proliferasyonu ve metastazında kritik bir rol oynamaktadır.…”
Section: Hedefe Yöneli̇k Tedavi̇ Yaklaşimi Ve Gelecek Perspekti̇flerunclassified